Affective and Psychomotor Education in Islamic Religious Learning through the Use of Technology during the Covid-19 Pandemic - Aat Royhatudin; Abdul Mujib; Naf'an Tarihoran (International Journal of Nusantara Islam, 2021)
This research highlights the understanding of religion, as well as actualizing affective and psychomotor education based on the ability to explore sources of knowledge, then be positive and responsible so that understanding of religion through online learning by utilizing technology, learners can communicate and interact with their teachers well, especially in the midst of a pandemic.By utilizing technology even if it does not involve direct interaction between teachers and learners who are factors and indicators of the success of education implemented, Islamic learning in the midst of the Covid-19 Pandemic through the use of technology can be done.The purpose of the research is to explain that PAI learning with the benefits of IT (Information Technology) can actualize religious understanding as a discipline integratively and comprehensively, so that for learners Mathla'ul Anwar improves affective and psychomotor education that is actualized in the daily life of learners.   Qualitative research methods with in-depth collection of interview results data and documentation related to research.The results showed that PAI learning by utilizing technology in the midst of a pandemic, learners were able to actualize comprehensively and effectively so that affective and psychomotor education of learners were able to contextualize religious guidance in accordance with the demands of the times with strict spiritual maintenance, while increasing individual piety and social piety in accessing information in accordance with the needs of society.